Implementasi Pembelajaran Diferensiasi Terhadap Gaya Belajar Siswa di SMP Negeri 1 Patumbak - Nispa Isnaini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the implementation of differentiated instruction in adapting to students' learning styles in the Islamic Education subject at SMP Negeri 1 Patumbak, particularly considering that some Islamic Education teachers have not yet applied this method. Differentiated instruction is an approach that adjusts teaching methods and strategies to meet the needs and characteristics of students, thereby enhancing the effectiveness of learning. The research method used in this study is descriptive qualitative, with data collection through observation, interviews, and documentation. The results indicate that although some teachers have begun to implement differentiated instruction by recognizing students' learning styles and using varied methods, there are still challenges, such as a lack of understanding among teachers about this concept and limitations in supporting resources. The application of differentiated instruction has been shown to improve students' motivation and understanding of Islamic Education material. Therefore, it is recommended that the school provide adequate training and support for teachers to optimally implement differentiated instruction.